SISTEM INFORMASI PENGINGAT KONTRAK KARYAWAN AEROFOOD ACS MENGGUNAKAN SMS GATEWAY (STUDI KASUS PADA KARYAWAN KONTRAK PT AEROFOOD INDONESIA BANDARA INTERNASIONAL SOEKARNO-HATTA, PAJANG, TANGERANG) - Zaqia Khana Meriza; Machudor Yusman; Dwi Sakethi; Aristoteles Aristoteles (Jurnal Pepadun, 2021)
Every month PT Aerofood Indonesia has a number of contract employees whose data needs to be managed and the follow-up determined by the HC (Human Capital) Development company. The HC determines the employee concerned for extending his contract or terminating his employment contract. The problem that occurs is the number of contract employees who annually have around 300 employees who need to check the expiration date of the work contract. Checking is still done manually by the HC by checking employee data from stored data files. In this study, an SMS Gateway based reminder information system was developed that can remind HC parties by sending a text message in the form of SMS reminders related to employee data that will be out of contract and send a SMS message to the employee that the contract will expire within one month before the expiry date of the contract, thus system can help the HC in speeding up the file preparation and decision process follow up on related employees.